High-toughness double-sided tape and preparation method thereof
By preparing special substrates, the refining of thermoplastic pellets and fillers is used, and the copolymerization film of rubber and acrylate is combined to increase vulcanizing agent and bicarbonate, the problem of insufficient toughness of double-sided tape is solved, and the preparation of high-tough double-sided tape is achieved.
Patent Information
- Application Number
- CN202510305087.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-15
AI Technical Summary
The existing double-sided tape is not tough enough, it is easy to brittle and tear, affecting its use effect and lifespan.
By preparing a special substrate, the thermoplastic pellets and fillers are used to combine a copolymer film of rubber and acrylate to increase the vulcanizing agent and bicarbonate to improve the toughness and bonding properties of the substrate.
The preparation of high-tough double-sided tape is achieved, reducing the risk of brittleness and tear, and improving the use effect and life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and in particular to a high-toughness double-sided adhesive tape and a preparation method thereof. Background Art
[0002] Double-sided tapes often become brittle and break during use due to insufficient toughness, which affects their use effect and life. The toughness of double-sided tapes is directly related to the substrate. Only when the substrate has good toughness can the toughness of double-sided tapes be good.
[0003] In the prior art, CN 112574693 A discloses a method for preparing a double-sided adhesive tape, which comprises the following steps: step S1: placing a release film on a pressing device for pressing; step S2: using a high-precision coating device to evenly coat a high-viscosity glue on the release surface of the release film, and after drying, laminating it with one side of a transparent PET substrate; and step S3: evenly coating the high-viscosity glue on the release surface of a release paper, and after drying, laminating it with the other side of the transparent PET substrate; wherein, in step S1, an embossed grid is formed on the release film after pressing, and the embossed grid consists of a plurality of longitudinal lines and transverse lines, and the transverse lines do not contact the longitudinal lines. CN 115058210 B discloses a manufacturing process for a double-sided adhesive tape, comprising an adhesive tape base layer and two release paper layers symmetrically connected and bonded to the upper and lower surfaces thereof, the double-sided adhesive tape comprising a release paper layer, an adhesive tape base layer, a first adhesive layer and a second adhesive layer, the first adhesive layer and the second adhesive layer are both filled between the release paper layer and the adhesive tape base layer, and a printed paper layer is connected between the first adhesive layer and the second adhesive layer, the double-sided adhesive tape is a layered structure and is composed of the above materials stacked on each other; multiple groups of adhesive tapes with the same specifications are obtained by one-time cutting, which is convenient to use and easy to tear off and stick; the adhesive tape base layer is selected from a transparent PET film or fiber paper tape with suitable tensile strength and reasonable dimensional stability, and the material is relatively easy to prepare, environmentally friendly and low in cost.
[0004] None of the above documents mentions a solution for improving the toughness of the double-sided tape by improving the substrate. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high-toughness double-sided adhesive tape and a preparation method thereof, wherein the double-sided adhesive tape has toughness.
[0006] To achieve the above object, the technical solution of the present invention is: A method for preparing a high-toughness double-sided adhesive tape comprises the following steps: Step (1): by weight, 10 to 20 parts of thermoplastic granules, 1 to 3 parts of fillers, 0.5 to 1 part of vulcanizing agent, 0.1 to 0.3 parts of lubricants and 0.1 to 0.5 parts of oils are mixed, and kneaded at 100° C. to 250° C. for 30 min to 50 min to obtain kneaded granules; Step (2): After fully mixing 10 to 20 parts by weight of an acrylic emulsion having a solid content of 20% to 40% and 1 to 3 parts of a natural rubber emulsion having a solid content of 30% to 60%, 0.01 to 0.05 parts of benzoyl peroxide-N,N-dimethylaniline and 0.01 to 0.05 parts of bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A, further apply the functional emulsion obtained in step (2) on both surfaces of coating A, and dry them at 60°C to 80°C in a functional gas atmosphere to obtain a film substrate; the functional gas is: containing 0.01 g / m 3 ~0.1g / m 3 nitrogen from sulfur particles; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with adhesive, baking until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0007] In order to obtain high-toughness double-sided tape, this solution has made the following improvements: 1. A special substrate is prepared. The special substrate of this scheme is a composite of a copolymer film of plastic and rubber and a plastic film to improve the toughness and strength of the substrate. Therefore, it is necessary to improve the bonding strength between the copolymer film of plastic and rubber and the plastic film, and then the following improvements are proposed: a. In step (1), the thermoplastic particles are kneaded with fillers, vulcanizers, etc. to ensure that the mixing is sufficient, which is beneficial to the coating operation after the kneaded particles are melted in step (3). At the same time, the prepared film substrate has a more uniform material distribution, including filler distribution and vulcanizer distribution. The filler contained in coating A can improve the strength of the coating; b. After the functional emulsion is coated, benzoic acid is added to the coating. Under the condition of acyl-N,N-dimethylaniline as an initiator, the copolymer film of rubber and acrylate is cured, and the copolymer film is combined with coating A to form a film substrate, wherein the acrylate emulsion, as the main component of the functional emulsion, itself has good compatibility with coating A. Furthermore, due to the presence of the vulcanizer on the contact surface of the coating A side to vulcanize the natural rubber component in the copolymer film, the strength of the film substrate is further enhanced. At the same time, under the action of the functional atmosphere, the mechanical properties of the copolymer film will be further enhanced. In addition, the main component of the copolymer film is acrylate, which has good affinity with the adhesive and is conducive to the adhesion of the adhesive.
[0008] 2. This solution improves the compatibility between the film substrate and the adhesive by adding bicarbonate. The main principle is that during the drying process in step (3), the bicarbonate dissolved in the emulsion precipitates during drying and then decomposes to produce carbon dioxide gas, which forms a large number of fine micropores on the surface of the film substrate. These micropores increase the surface roughness of the film substrate, thereby improving the adhesion ability of the adhesive.
[0009] Preferably, in step (1), the thermoplastic particles are one or more of low-density polyethylene particles, nylon particles, polyvinyl chloride particles, chlorinated polyethylene particles, polypropylene particles, polystyrene particles, and polycarbonate particles.
[0010] Preferably, in step (1), the filler is one or more of calcium carbonate powder, silicon dioxide powder, aluminum oxide powder, magnesium oxide powder, carbon black powder, and zinc oxide powder.
[0011] Preferably, in step (1), the vulcanizing agent is one of sulfur powder, metal oxide vulcanizing agent or resin vulcanizing agent.
[0012] Preferably, in step (1), the lubricant is one of sodium stearate, zinc stearate, magnesium stearate or calcium stearate.
[0013] Preferably, in step (1), the oil agent is one of soybean oil, motor oil or paraffin oil.
[0014] Preferably, in step (2), the acrylic ester emulsion is a combination of one or more of methyl acrylate emulsion, butyl methacrylate emulsion, isooctyl acrylate, and isooctyl methacrylate.
[0015] Preferably, in step (2), the bicarbonate is one of calcium bicarbonate or sodium bicarbonate.
[0016] Preferably, in step (3), the functional gas is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 100°C to 120°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.01 g / m 3 ~0.1g / m 3 functional gas.
[0017] Preferably, in step (3-1), the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1% to 10%, and the dispersant is one of PEG-400, sodium dodecyl sulfate, glycerol, and ethanol.
[0018] The function of the dispersant is to disperse the sulfur particles generated by the reaction so that the sulfur suspension has better uniformity.
[0019] Preferably, in step (3), the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the thickness of the film substrate is 0.15 mm to 0.5 mm, and the thickness ratio of the copolymer film to the coating A is 0.5 to 1:1.
[0020] Preferably, in step (3), the gas flow rate of the functional gas atmosphere is 1m 3 / min~3m 3 / min.
[0021] The gas flow rate should not be too large, as it may cause problems such as rapid water loss, incomplete reaction of the copolymer film, and incomplete vulcanization; too small a flow rate may cause excessive vulcanization, hardening of the copolymer film, shrinkage and wrinkles.
[0022] Preferably, the baking temperature in step (4) is 60° C. to 80° C.; and the adhesive is an acrylate.
[0023] This solution also provides a double-sided adhesive prepared by the above preparation method.
[0024] Compared with the prior art, the present invention achieves the following beneficial effects: 1. It has high toughness and is not easy to become brittle and break.
[0025] 2. A special substrate is prepared by compounding a copolymer film of plastic and rubber with a plastic film, and considering the bonding strength between the copolymer film and the plastic film, a vulcanizer is pre-integrated into the plastic film; a rough surface is obtained by adding bicarbonate when preparing the copolymer film, further improving the bonding ability between the substrate and the adhesive. DETAILED DESCRIPTION
[0026] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0027] Embodiment 1, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 3m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0028] Embodiment 2, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 10 parts of chlorinated polyethylene particles, 2 parts of a mixture of silicon dioxide powder, aluminum oxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.5 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 100° C. for 30 minutes to obtain kneaded particles; Step (2): After fully mixing 20 parts by weight of butyl methacrylate emulsion having a solid content of 40% and 3 parts of natural rubber emulsion having a solid content of 60%, 0.04 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 80°C and a gas flow rate of 2 m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.5 mm, and the thickness ratio of the copolymer film to the coating A is 1:1; The functional gas is: containing 0.05g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 5%, and the dispersant is ethanol; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 120°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.05 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 80° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0029] Embodiment 3, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 10 parts of nylon particles, 1 to 3 parts of a mixture of calcium carbonate powder, silicon dioxide powder, aluminum oxide powder, and magnesium oxide powder in equal weight ratio, 0.5 parts of sulfur powder, 0.2 parts of calcium stearate, and 0.4 parts of soybean oil are mixed, and kneaded at 230° C. for 30 minutes to obtain kneaded particles; Step (2): After thoroughly mixing 10 parts by weight of isooctyl acrylate with a solid content of 20% and 1 part of natural rubber latex with a solid content of 40%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional latex; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 2 m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.4 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 3%, and the dispersant is glycerol; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 105°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.08 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0030] Embodiment 4, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 13 parts of polypropylene particles, 2 parts of a mixture of calcium carbonate powder, silicon dioxide powder, aluminum oxide powder, magnesium oxide powder, carbon black powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.1 parts of calcium stearate and 0.5 parts of paraffin oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 18 parts by weight of butyl methacrylate emulsion with a solid content of 25% and 1 part to 3 parts of natural rubber emulsion with a solid content of 35%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.03 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 1 m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.35 mm, and the thickness ratio of the copolymer film to the coating A is 0.6:1; The functional gas is: containing 0.08g / m 3The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.3%, and the dispersant is sodium dodecyl sulfate; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 118°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.08 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0031] Comparative Example 1, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 2 parts of a mixture of calcium carbonate powder, silicon dioxide powder, aluminum oxide powder, magnesium oxide powder, and zinc oxide powder in equal weight ratio, 0.5 parts of sulfur powder, 0.2 parts of calcium stearate, and 0.3 parts of soybean oil are mixed, melted, and coated as a film substrate; Step (2): placing the film substrate obtained in step (1) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 60°C to 80°C until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0032] Comparative Example 2, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): after fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 40% and 2 parts of natural rubber emulsion with a solid content of 60%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.03 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (2): Apply the functional emulsion obtained in step (1) at 70°C and a gas flow rate of 3m 3 / min functional gas atmosphere, drying to obtain a thin film substrate; The functional gas is: containing 0.05g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (2-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.3%, and the dispersant is PEG-400; Step (2-2): spray-dry the sulfur suspension under nitrogen conditions at 120°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.5 g / m 3 Functional gas; Step (3): placing the film substrate obtained in step (3) on a coating device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0033] Comparative Example 3, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed to prepare a mixture; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the mixture obtained in step (1) and apply it to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat at 70°C and a gas flow rate of 3m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0034] Comparative Example 4, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 3m 3 / min in a nitrogen atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0035] Comparative Example 5, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 3m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0036] Comparative Example 6, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of silicon dioxide powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil were mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 70°C and a gas flow rate of 3m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0037] Comparative Example 7, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 90°C and a gas flow rate of 5 m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0038] Comparative Example 8, a method for preparing a high-toughness double-sided adhesive tape, comprising the following steps: Step (1): by weight, 15 parts of polycarbonate particles, 3 parts of a mixture of silicon dioxide powder, magnesium oxide powder and zinc oxide powder in equal weight ratio, 0.8 parts of sulfur powder, 0.2 parts of calcium stearate and 0.3 parts of soybean oil are mixed, and kneaded at 180° C. for 40 minutes to obtain kneaded particles; Step (2): After fully mixing 15 parts by weight of methyl acrylate emulsion with a solid content of 30% and 2 parts of natural rubber emulsion with a solid content of 50%, 0.03 parts of benzoyl peroxide-N,N-dimethylaniline and 0.05 parts of calcium bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A. Further apply the functional emulsion obtained in step (2) on both surfaces of coating A and heat the mixture at 50°C and a gas flow rate of 0.5 m 3 / min functional gas atmosphere, drying to obtain a film substrate; the film substrate comprises a copolymer film and a coating A, and the coating A is located between two layers of copolymer films; the film substrate has a thickness of 0.3 mm, and the thickness ratio of the copolymer film to the coating A is 0.5:1; The functional gas is: containing 0.03g / m 3 The nitrogen functional gas of the sulfur granules is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1%, and the dispersant is PEG-400; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 110°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.03 g / m 3 Functional gas; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with a pressure-sensitive acrylic adhesive APSA adhesive, baking at 70° C. until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
[0039] Detection method: Adhesion ability test: Refer to the test method specified in HG / T 3658-2018 Double-sided pressure-sensitive adhesive tape to test the peel strength in normal state and wet heat aging state; the test result must be greater than 2.5N / cm.
[0040] Toughness test: The mechanical properties of the film substrates prepared in Examples 1-4 and Comparative Examples 1-8 were tested with reference to the test methods specified in GB / T 7124 and GB / T 1040, and the tensile strength (N / cm) and the tensile strain at break (%) were recorded; the puncture strength of the film substrate was determined with reference to GB / T 10004-2008, and the performance was divided into Grade 1, Grade 2 and Grade 3 from best to worst.
[0041] The test results are shown in Table 1.
[0042] Table 1 Detection comparison results
[0043] It can be seen from the data in Table 1 that Examples 1-4 have better performance, and Comparative Examples 1-8 have individual data with better indicators, but the overall performance is poor.
[0044] The difference between Comparative Example 1 and Example 1 is that the film substrate of Comparative Example 1 is only similar to the coating A in Example 1, and no functional emulsion is applied, that is, no copolymer film. The copolymer film is a copolymer of polypropylene and natural rubber, and has high toughness. Comparative Example 1 only has the coating A described in Example 1, and has low tensile strength, small fracture strain, and low toughness. The difference between Comparative Example 2 and Example 1 is that the coating A is not applied, and the fracture tensile strain is too high, which will cause the double-sided adhesive to deform due to force during use.
[0045] The difference between Comparative Example 3 and Example 1 is that step (1) is not mixed, which may be due to poor uniformity of the mixture, resulting in poor uniformity of force, leading to a decrease in overall performance; the difference between Comparative Example 4 and Example 1 is that step (3) does not use functional gas, that is, the copolymer film part of the film substrate is not completely vulcanized, resulting in low performance; the difference between Comparative Example 5 and Example 1 is that no bicarbonate is added in step (2), which reduces the surface roughness of the film substrate finally obtained, reduces the adhesion effect of the adhesive, and leads to a decrease in adhesion; the difference between Comparative Example 6 and Example 1 is that no vulcanizing agent component is added in step (1) , magnesium oxide and zinc oxide, magnesium oxide and zinc oxide also have a certain vulcanization effect. The lack of these components makes the vulcanization effect of the coating A and the copolymer film in the film substrate poor, the bonding effect deteriorates, and the film substrate is easily delaminated during use, resulting in poor adhesion and decreased mechanical properties; the difference between comparative example 7 and example 1 is that in step (3), the functional gas flow rate is too large and the temperature is too high, which causes the copolymer film to cure too quickly and the vulcanization reaction effect to deteriorate; the difference between comparative example 8 and example 1 is that in step (3), the functional gas flow rate is too small and the temperature is too low, which causes the copolymer film to cure too slowly and the vulcanization reaction to be excessive.
[0046] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high-toughness double-sided adhesive tape, characterized in that: The following steps are involved: Step (1): by weight, 10 to 20 parts of thermoplastic granules, 1 to 3 parts of fillers, 0.5 to 1 part of vulcanizing agent, 0.1 to 0.3 parts of lubricants and 0.1 to 0.5 parts of oils are mixed, and kneaded at 100° C. to 250° C. for 30 min to 50 min to obtain kneaded granules; Step (2): After fully mixing 10 to 20 parts by weight of an acrylic emulsion having a solid content of 20% to 40% and 1 to 3 parts of a natural rubber emulsion having a solid content of 30% to 60%, 0.01 to 0.05 parts of benzoyl peroxide-N,N-dimethylaniline and 0.01 to 0.05 parts of bicarbonate are added, and the mixture is stirred evenly to obtain a functional emulsion; Step (3): Melt the kneaded particles obtained in step (1) and apply them to obtain coating A, further apply the functional emulsion obtained in step (2) on both surfaces of coating A, and dry them at 60°C to 80°C in a functional gas atmosphere to obtain a film substrate; the functional gas is: containing 0.01 g / m 3 ~0.1g / m 3 nitrogen from sulfur particles; Step (4): placing the film substrate obtained in step (3) on a coating and gluing device, coating both sides of the film substrate with adhesive, baking until the water content is less than 10%, covering with release paper, winding or stacking, and then cutting to obtain a high-toughness double-sided tape.
2. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: In step (1), the thermoplastic granules are one or more of low-density polyethylene particles, nylon particles, polyvinyl chloride particles, chlorinated polyethylene particles, polypropylene particles, polystyrene particles, and polycarbonate particles; the filler is one or more of calcium carbonate powder, silicon dioxide powder, aluminum oxide powder, magnesium oxide powder, carbon black powder, and zinc oxide powder; the vulcanizing agent is one of sulfur powder, metal oxide vulcanizing agent, or resin vulcanizing agent; the lubricant is one of sodium stearate, zinc stearate, magnesium stearate, or calcium stearate; and the oil is one of soybean oil, motor oil, or paraffin oil.
3. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: In step (2), the acrylate emulsion is a combination of one or more of methyl acrylate emulsion, butyl methacrylate emulsion, isooctyl acrylate, and isooctyl methacrylate; and the bicarbonate is one of calcium bicarbonate and sodium bicarbonate.
4. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: In step (3), the functional gas is prepared by the following method: Step (3-1): introducing excess sulfur dioxide gas into a saturated sodium sulfide solution and rapidly stirring to obtain a sulfur suspension; Step (3-2): spray-dry the sulfur suspension under nitrogen conditions at 100°C to 120°C to obtain sulfur-containing nitrogen gas, then add dry nitrogen gas to dilute the sulfur-containing nitrogen gas to a sulfur particle concentration of 0.01 g / m 3 ~0.1g / m 3 functional gas.
5. The method for preparing the high-toughness double-sided adhesive tape according to claim 4, characterized in that: In step (3-1), the saturated sodium sulfide solution contains a dispersant with a mass fraction of 0.1% to 10%, and the dispersant is one of PEG-400, sodium dodecyl sulfate, glycerol, and ethanol.
6. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: In step (3), the film substrate comprises a copolymer film and a coating A, wherein the coating A is located between two layers of copolymer films; the thickness of the film substrate is 0.15 mm to 0.5 mm, and the thickness ratio of the copolymer film to the coating A is 0.5 to 1:
1.
7. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: In step (3), the gas flow rate of the functional gas atmosphere is 1m 3 / min~3m 3 / min.
8. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: The baking temperature in step (4) is 60°C to 80°C.
9. The method for preparing the high-toughness double-sided adhesive tape according to claim 1, characterized in that: The adhesive in step (4) is an acrylic adhesive.
10. A double-sided adhesive tape prepared by the method for preparing a high-toughness double-sided adhesive tape as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Double-sided adhesive tape manufacturing process
CN115058210B